2020
DOI: 10.1111/jnc.15207
|View full text |Cite
|
Sign up to set email alerts
|

Brain endothelial cells metabolize glutamate via glutamate dehydrogenase to replenish TCA‐intermediates and produce ATP under hypoglycemic conditions

Abstract: The endothelial cells of the blood–brain barrier participate in the regulation of glutamate concentrations in the brain interstitial fluid by taking up brain glutamate. However, endothelial glutamate metabolism has not been characterized, nor is its role in brain glutamate homeostasis and endothelial energy production known. The aim of this study was to investigate endothelial glutamate dehydrogenase (GDH) expression and glutamate metabolism and probe its functional significance. The primary brain endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Glutathione (GSH), superoxide dismutase (SOD), and glutathione peroxidase (GPX) are major antioxidant molecules in ECs [ 28 ]. A recent report showed that brain ECs directly absorb and metabolize glutamate and utilize the resulting α-ketoglutarate in the tricarboxylic acid cycle, ultimately producing ATP in the absence of glucose [ 29 ]. Our “scMetabolism” analysis shows that ECs from DMD mut showed high activities of glycine, serine, and threonine metabolism, glutathione metabolism, and alanine, aspartate, and glutamate metabolism, but low activity of cysteine and methionine metabolism compared to ECs from control muscle ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Glutathione (GSH), superoxide dismutase (SOD), and glutathione peroxidase (GPX) are major antioxidant molecules in ECs [ 28 ]. A recent report showed that brain ECs directly absorb and metabolize glutamate and utilize the resulting α-ketoglutarate in the tricarboxylic acid cycle, ultimately producing ATP in the absence of glucose [ 29 ]. Our “scMetabolism” analysis shows that ECs from DMD mut showed high activities of glycine, serine, and threonine metabolism, glutathione metabolism, and alanine, aspartate, and glutamate metabolism, but low activity of cysteine and methionine metabolism compared to ECs from control muscle ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported GDH activity in the cerebral capillaries and endothelial cells. 57 Interestingly, metabolism of glutamate through OXPHOS was found to be increased in the absence of glucose in the brain endothelial cells. 57 In mammalian cells with impaired mitochondrial respiration resulting from mitochondrial DNA mutations, elevated glutamine metabolism was found to be critical for energy production and for anaplerosis.…”
Section: Discussionmentioning
confidence: 99%
“…57 Interestingly, metabolism of glutamate through OXPHOS was found to be increased in the absence of glucose in the brain endothelial cells. 57 In mammalian cells with impaired mitochondrial respiration resulting from mitochondrial DNA mutations, elevated glutamine metabolism was found to be critical for energy production and for anaplerosis. 58 Supporting our respiration measurements, we found that the activity of GDH was increased in aged BMVs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides astrocytes and neurons, EAATs have been identified in the endothelial cells of brain vasculature ( Hawkins et al, 2006 ; Hawkins, 2009 ), indicating a potential important role of vascular endothelial cells in the regulation of glutamate dynamics. In fact, it has been described that glutamate carriers are present in the luminal membrane of endothelial cells and EAATs in the abluminal membrane ( Cohen-Kashi-Malina et al, 2012 ; Hinca et al, 2021 ). The distributions of glutamate carriers and EAATs in endothelial cells could allow glutamate diffusion from brain tissue to blood following its concentration gradient.…”
Section: Specific Biomarkers For Disease Burden and Outcomes For Pati...mentioning
confidence: 99%